2022
DOI: 10.1038/s41577-022-00786-1
|View full text |Cite
|
Sign up to set email alerts
|

Allergen immunotherapy: past, present and future

Abstract: Allergen immunotherapy is a form of therapeutic vaccination for established IgE-mediated hypersensitivity to common allergen sources such as pollens, house dust mites and the venom of stinging insects. The classical protocol, introduced in 1911, involves repeated subcutaneous injection of increasing amounts of allergen extract, followed by maintenance injections over a period of 3 years, achieving a form of allergen-specific tolerance that provides clinical benefit for years after its discontinuation. More rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 160 publications
2
80
0
3
Order By: Relevance
“…The final Editor's Choice article evaluates the allergenicity and immunogenicity of a hybrid molecule containing T-cell epitopes from three major house dust mite allergens, Der p 1, Derp 2 and Der p 23, as a novel therapeutic option for allergen immunotherapy (AIT). 7 AIT is the only clinical management of allergies that can control the progression of these immune-mediated diseases by inducing immunological tolerance 8,9 Therapies with T-cell-targeted molecules can significantly impact the safety and efficacy of AIT, making them favourable alternatives to natural extracts.…”
Section: Biological Therapy Practice Biomarkers Of Severe Asthma and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The final Editor's Choice article evaluates the allergenicity and immunogenicity of a hybrid molecule containing T-cell epitopes from three major house dust mite allergens, Der p 1, Derp 2 and Der p 23, as a novel therapeutic option for allergen immunotherapy (AIT). 7 AIT is the only clinical management of allergies that can control the progression of these immune-mediated diseases by inducing immunological tolerance 8,9 Therapies with T-cell-targeted molecules can significantly impact the safety and efficacy of AIT, making them favourable alternatives to natural extracts.…”
Section: Biological Therapy Practice Biomarkers Of Severe Asthma and ...mentioning
confidence: 99%
“…The final Editor's Choice article evaluates the allergenicity and immunogenicity of a hybrid molecule containing T‐cell epitopes from three major house dust mite allergens, Der p 1, Derp 2 and Der p 23, as a novel therapeutic option for allergen immunotherapy (AIT) 7 . AIT is the only clinical management of allergies that can control the progression of these immune‐mediated diseases by inducing immunological tolerance 8,9 Therapies with T‐cell‐targeted molecules can significantly impact the safety and efficacy of AIT, making them favourable alternatives to natural extracts.3 A series of clinical trials have already demonstrated that hypoallergenic T‐cell epitope‐based allergens can compose safe and effective therapeutic formulations for AIT. This study aimed to generate a hypoallergenic hybrid molecule containing T‐cell epitopes from these three major allergens, Der p 1, Der p 2 and Der p 23.…”
mentioning
confidence: 99%
“…AIT can be applied through multiple routes depending on the type of allergic disease and the source of sensitization [ 19 ]. Likewise, the selected application route leads to particularities in the antigen-presentation process, reflected in differences in efficacy and safety [ 20 ].…”
Section: Overview Of Ait Featuresmentioning
confidence: 99%
“…Subcutaneous immunotherapy (SCIT) is the oldest and most frequently used application route of AIT, which has been employed for more than a century [ 7 ]. SCIT is regarded as a safe and valid therapy for several allergic diseases including venom allergy, AR, and allergic asthma [ 19 ]. While adverse reactions occur in up to 71% of patients, severe side effects are rare [ 22 ].…”
Section: Overview Of Ait Featuresmentioning
confidence: 99%
See 1 more Smart Citation